State-Aiding, Empire-Building or Multitude Fulfilling? An Anonymous Role in International Politics - Tynes, Robert M (AoIR Selected Papers of Internet Research, 2016)
GhostSec is out there, fighting. The Anonymous cell is hack-attacking politically violent Islamic groups, including Al-Shabaab, Boko Haram and the Islamic State (IS). GhostSec is intent upon exposing extremist twitter accounts and taking down their web face presence. The goal seems to be to prevent the "bad guys" from using cybertools to perpetuate their violence in Somalia, Nigeria, Libya and Syria. As such, GhostSec is a humanitarian cause that prevents the territorialization of cyberspace by those groups who are against the liberal ideology of freedom of the individual. It is a noble cause, a cyber battle, almost mythic. Is it so simple, though–good vs. bad? And what is the desired outcome? This article will explore the role of GhostSec in international politics, specifically examining whether the Anonymous group is State-Aiding, Empire-Building or Multitude-Fulfilling (Hardt and Negri 2000). Even though the trickster lulz Anonymous may jump out and raspberry the world while it "takes down" a terrorist group’s web body, it still must consider the socio-political forces vying for the power that it generates. Who benefits from its antics, who loses?